(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the role and importance of the auxiliary history science of faleristics in the museum sphere, as well as the scientific classification and description of objects and subjects of faleristics, their place of origin and specific features in the museum. The study examined the order of state registration of faleristic objects included in the museum subjects